Optimization Of Digital Marketing Utilization Based on E-Commerce to Enhance Sales and Marketing - Adinda Dwi Larasati; Anita Diana (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
This study aims to develop and optimize digital marketing strategies through an e-commerce–based system for the Charming Charlotte accessories business in order to enhance sales effectiveness and competitive advantage. The problems identified include the limited use of marketing media that rely solely on social media, the absence of a website capable of supporting online transactions, and manual order recording that increases the risk of data processing errors. This research employs the Business Model Canvas (BMC) to formulate the business model, utilizes Unified Modeling Language (UML) to model system processes, and develops an e-commerce website based on a Content Management System (CMS) using WordPress and WooCommerce integrated with Search Engine Optimization (SEO) techniques. The results indicate that the implementation of the e-commerce system effectively expands marketing reach, improves transaction management efficiency, provides more systematic sales reports, and enhances business visibility through search engine optimization. This research proves that the simultaneous integration of CMS, BMC, UML, and SEO is effective in strengthening digital marketing performance for small businesses.